Kreativitas Guru dalam Pembelajaran IPS di SMP Negeri 10 Metro - Messy Amalia Resky; Anita Lisdiana (STKIP PGRI Bandar Lampung, 2023)
This study describes and describes the creativity of teachers in social studies learning. The type of research used by the researcher is field qualitative research (field research) with a qualitative approach. The data collection technique used is observation, making observations related to teacher creativity in social studies learning, interviews with resource persons, namely teachers, students, school principals, and documentation used by researchers to obtain information sourced from written documents in the form of books, magazines, journals, diaries. and so forth. Teacher creativity is needed in order to maximize learning. The results of the study indicate that there are forms of teacher creativity in social studies learning, namely: (1) Fluency, namely there are new ideas in learning, (2) Flexibility, namely being flexible in learning, (3) Being able to read the character of students, (4) Variation in using learning methods such as question and answer methods, discussions, assignments, varied lectures, and role play. (5) Varied use of learning media, such as internet, whatsapp group, google classroom, google form, youtube, interactive power point, film, DVD, and zoom meeting. (6) Have a good and inspiring character. There are factors supporting and inhibiting teacher creativity in social studies learning. Factors supporting the creativity of teachers, namely there is support from the school, the availability of infrastructure, the activity of teachers and students in the learning process. The inhibiting factors are the limitations of face-to-face learning, the different abilities of students, and the difficulty of students' internet network access.